Lighting Installation System Design in the Parking Area of Prof. Dr. Soekandar Mojokerto Regional Hospital Based on Dialux Software: Desain Sistem Instalasi Penerangan pada Area Parkir RSUD Prof Dr Soekandar Mojokerto berbasis Dialux Software - Budi Utomo; Dwi Ajiatmo; Hidayatul Nurohmah; Machrus Ali (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2026)
This study aims to design an optimal lighting installation system for the parking area of RSUD Prof. Dr. Soekandar Mojokerto by using DIALux Evo as a lighting simulation tool. The existing lighting system employs three 150 W High Pressure Sodium (HPS) lamps and does not meet the parking area lighting standard specified in SNI 7391:2008. The simulation results of the existing condition indicate an average illuminance of 35.3 lux, an average luminance of 3.37 cd/m², a uniformity ratio of 0.005, and a Unified Glare Rating (UGR) of 25. To improve the lighting performance, a redesign was carried out using 17 units of 57 W LED lamps. The simulation results of the proposed design show significant improvement, with an average illuminance of 96.5 lux, an average luminance of 9.21 cd/m², a uniformity ratio of 0.37, and a glare level of 19. Although the energy consumption increased from 5.4 kWh to 11.628 kWh, this increase is proportional to the improvement in lighting quality. The results indicate that the use of LED lamps provides brighter, more uniform, and more visually comfortable lighting while complying with the applicable standards. Therefore, the DIALux Evo-based lighting design is recommended for implementation in hospital parking areas and similar public facilities.